Factors Influencing Online Gambling Acceptance Among Thai Undergraduate Students - Pakawich, Damrongkiattisak (2023)
this study aims to examine the factors that have impacts on Thai undergraduate students’ behaviour. Thus, the technological, psychological, and personal factors will be used to create a comprehensive model of TAM (Technology Acceptance Model) to explain why Thai undergraduate students tend to gamble online